Metabolism as a biomarker for treatment success in anti-amyloid therapy: A case report - Kirk C. Wilhelmsen; Pierre-François D’Haese; Marc W. Haut; Gary D. Marano; Rashi I. Mehta; Xiaofei Wang; Melanie Ward; Mark Miller; Umer Najib; R. Osvaldo Navia; Cierra M. Keith; Ali Rezai (NeuroImage: Reports)
This case report investigates the potential use of metabolism as a sensitive biomarker in monitoring the effectiveness of anti-amyloid therapy in a patient with mild cognitive impairment due to early Alzheimer's disease. The study centers around a 74-year-old male patient treated with aducanumab, a monoclonal antibody developed for anti-amyloid therapy. Alongside an expected decline in cerebral amyloid monitored using PET amyloid tracers, we observed significant improvements in the patient's brain metabolic activity, measured via 18-fluorodeoxyglucose positron emission tomography (FDG PET). Despite limitations posed by the single-patient case study, the findings invite further research and consider the utilization of FDG PET as a surrogate for clinically meaningful changes in the treatment of early Alzheimer's disease. These findings suggest the potential for more personalized and effective therapeutic interventions.